Graphene oxide/core–shell structured metal–organic framework nano-sandwiches and their derived cobalt/N-doped carbon nanosheets for oxygen reduction reactions. Issue 21 (12th April 2017) - Wei, Jing; Hu, Yaoxin; Liang, Yan; Kong, Biao; Zheng, Zhanfeng; Zhang, Jin; Jiang, San Ping; Zhao, Yongxi; Wang, Huanting
Abstract : A metal–organic framework (MOF) seed-mediated deposition route is developed to synthesize graphene oxide/core–shell structured MOF nano-sandwiches. Abstract : A metal–organic framework (MOF) seed-mediated deposition route is developed to synthesize MOF/graphene oxide (GO)/MOF nano-sandwiches with core–shell structured MOF ( i.e. ZIF-8@ZIF-67) crystals uniformly distributed on GO. Due to the well controllable growth rate, ZIF-8 seeds are first deposited on GO. Then, ZIF-67 species are selectively deposited on the surface of ZIF-8 to form core–shell structures owing to their similar crystal structure and unit cell parameter. Compared with the direct deposition of ZIF-67 crystals on GO, this MOF seed-mediated synthesis can effectively prevent the over-growth and inhomogeneous distribution of ZIF-67 crystals. The GO/core–shell MOF composites are further demonstrated to be an excellent precursor for cobalt/N-doped carbon nanosheets, which are efficient nonprecious metal catalysts for oxygen reduction reactions, and exhibit a high onset potential (∼0.93 V versus reversible hydrogen electrode, vs. the RHE) and large kinetic current density (∼101 mA mg −1 at 0.80 V vs. the RHE). Such novel carbon materials derived from the core–shell structured MOF also show better catalytic performance than those derived from both GO/ZIF-8 and GO/ZIF-67 prepared under the same conditions. This work offers an alternative strategy to develop MOF-derived carbon-based composites using GO/core–shell structured MOFs as a kind of fresh precursors.